Elasticity of lawsonite and seismological signature of metamorphism and water cycling in the subducting oceanic crust. (24th February 2014) - Reynard, B.; Bass, J. D.
Abstract The elastic properties of lawsonite determined from equations of state, Brillouin scattering, acoustic velocity measurements, and first‐principles calculations are reviewed. Equations of state are essential for thermodynamic modelling of phase equilibrium at high pressure. Elastic tensor determinations allow calculation of the seismic properties of isotropic rocks, and of anisotropic rocks when combined with CPO determinations. Potential effects of low‐T, high‐P phase transitions in lawsonite on extrapolations to deep‐Earth conditions are discussed. Seismological data suggest that metamorphic zoning in active cold subduction zones can be resolved as low velocity layers down to 250 km. Mineral physics and phase equilibria indicate that lawsonite is the best candidate for explaining such low velocities. These layers are likely the image of water recycling to the deep mantle in subduction zones.